MEK Inhibitors in Combination with Immune Checkpoint Inhibition: Should we be Chasing Colorectal Cancer or the KRAS Mutant Cancer - Julius Strauss (Global Journal of Cancer Therapy - Peertechz Publications, 2017)
In the past few years, immunotherapy, particularly immune checkpoint inhibitors, have redefi ned standard of care cancer treatment for numerous malignancies. However, despite the wealth of promising data and great enthusiasm, the vast majority of cancer patients still fail to respond to these therapies as single agents. In tumors which are thought of as immunogenic (e.g. renal cell, urothelial, non-small cell lung cancer (NSCLC)) the response rate to single agent immune checkpoint inhibition seems to be around 20% [1], but in still other tumors generally thought of as non-immunogenic the response rate seems to be far less. In these non-immunogenic tumor types much focus has been given to the subset of patients with high microsatellite instability (MSI-H) or mismatch repair defi cient tumors which have been shown to have relatively high response rates to single agent PD-1 therapy [2]. But patients with MSI tumors often make up only a tiny fraction of patients with these non-immunogenic tumors. One clear example of this is colorectal cancer (CRC) where only 15% of patients have MSI-H disease and only 4% of patients with metastatic disease have MSI-H tumors [3]. Therefore, hundreds of trials are currently underway evaluating the combination of immune checkpoint inhibition with other treatment options in an effort to increase the percentage of patients both with immunogenic and non-immunogenic tumors who will respond to immune checkpoint inhibition. One such trial was recently conducted in CRC patients with microsatellite stable (MSS) disease.